Nutritional Needs in Court Tennis Athletes - Jonatan, Jonatan Hutasoit; Nurkadri; Charly Manurung; Mars Arianja Tarigan; Robert A Simatupang; Jannery Ginting (Jurnal Pendidikan Jasmani (JPJ), 2023)
This study explores the specific nutritional needs of field tennis athletes, a sport discipline that demands strength, endurance, agility, and high concentration. The purpose of this study was to understand how proper dietary intake can support physical fitness, maximum performance, efficient recovery, and general health of athletes. The research methodology involved a detailed survey of a number of field tennis athletes, as well as an analysis of related scientific literature and several journals. The parameters considered include the necessary nutritional composition, caloric intake, proper meal timing, and other special aspects relating to the nutritional needs of court tennis athletes. The results showed that appropriate nutrient intake is a key element in maintaining and improving the performance of court tennis athletes. An understanding of the need for carbohydrates, proteins, healthy fats, vitamins, and minerals is important in maintaining energy, speeding recovery, and optimizing strength and endurance. In conclusion, field tennis athletes need a carefully planned diet to reach their full potential. This research provides useful guidance for athletes, coaches, and health professionals in designing nutrition strategies that fit the individual needs of athletes.